Oral anticoagulant use among Medicare patients newly diagnosed with venous thromboembolism (VTE): Factors associated with treatment status - James C. Coons; Aolin Wang; Dominick Latremouille-Viau; Cristina Russ; Dong Cheng; Robert Stellhorn; Feng Dai; David R. Steffen; Abigail Zion; Serina Deeba; Dionne M. Hines (PLoS ONE, 2025)
Objective This study aimed to describe oral anticoagulant (OAC) use among patients with venous thromboembolism (VTE). Materials and methods This study included Medicare fee-for-service beneficiaries (data from 1/1/2014-12/31/2019) newly diagnosed with VTE. Factors associated with being untreated with OACs in the first month from VTE (vs. OAC-treated), with receiving direct-acting OACs ([DOACs] vs. warfarin), and with extended OAC treatment (>3 months) were assessed using multivariable logistic regressions. Results Overall, 169,928 patients with VTE (50.3% OAC-untreated) were included. Among the 49.7% OAC-treated patients, 74.0% used DOACs and 62.5% had extended OAC treatment. Factors associated with being untreated with OACs in the first month from VTE (odds ratio; 95% confidence interval) included Hispanic ethnicity (vs. White;1.35; 1.29–1.42), having part D low-income subsidy (1.14; 1.07, 1.20), and comorbidities such as cardiovascular diseases. Among the OAC-treated cohort, patients with index VTE diagnosis in the emergency room (vs. outpatient) setting had higher odds of receiving DOAC vs. warfarin; patients with pulmonary embolism diagnosis (vs. deep vein thrombosis) had higher odds of extended OAC treatment. Conclusions In this study of Medicare patients newly diagnosed with VTE, half of the patients were not treated with OAC in the first month from initial diagnosis. Factors such as Hispanic ethnicity, having low-income subsidy, and comorbidity burden were found to be associated with being untreated with OAC. Among OAC-treated patients, the majority were treated with DOAC vs. warfarin. Interestingly, more than a third of OAC-treated patients were not treated beyond 3 months, which warrants further investigation.